Evaluation of oral mucositis in oral cancer patients undergoing radiotherapy - Bajracharya, Barsha; Bhattacharyya, Subrata; Poudel, Pratibha (Journal of Chitwan Medical College, 2018)
Introduction: The present study was conducted to evaluate oral mucositis in oral cancer patients receiving head and neck radiotherapy. Methods: Sixty oral cancer patients who had received at least 40 grays of radiation were included in the study. Mucositis was scored by oroscopy using WHO scale. Grades of mucositis were then compared with total dose of radiation received by the patients. Results: The cases were receiving the mean cumulative dose of standard radiation therapy of 2Gy per fraction, 5 fractions per week. All the patients developed oral mucositis. The majority had grade I mucositis, followed by grade III, II and IV. The grade of mucositis was directly proportional to the dose of radiation exposure. Conclusion: Oral mucositis occurs among all the patients undergoing head and neck radiotherapy and grade of mucositis is proportional to the dose of radiation exposure.